National perspectives on the global Second World War
1 online resource
Keywords: "This collection of essays, written by authors of different nationalities, explores the experiences of the countries that were not numbered among the Second World War's major belligerents, including colonies, "lesser" powers, and neutral nation states. National Perspectives on the Global Second World War is an essential contribution to the study of the Second World War and will be of particular interest to scholars of imperial and colonial history, military history, and global history"--